Efficacy and safety of intravenous iron therapy in heart failure patients with iron deficiency: a systematic review and meta-analysis of randomized controlled trials (Journal of Medical Science, 2025)
Introduction. Heart failure is a diverse life-threatening condition with complex biology and demanding therapeutic goals. Even when anemic patients are excluded, up to 59% of heart failure patients have low ferritin levels, making them especially vulnerable to iron deficiency. We aim to explore the benefits and safety of intravenous iron therapy among patients with heart failure and iron deficiency. Material and methods. We have searched the literature on PubMed (MEDLINE), Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science (WoS), and EMBASE until 31st August, 2023. We used RevMan V. 5.4 to pool dichotomous data using a risk ratio (RR) with a 95% confidence interval (CI). This review has been registered and published in PROSPERO (CRD42023471419) Results. Fourteen randomized controlled trials with 6,626 patients were included. The intravenous iron group was favored over the control group in reducing hospital admissions for heart failure (first event) (RR= 0.83, 95% CI 0.71 to 0.97; p = 0.02) and (total events) (RR= 0.81, 95% CI 0.74 to 0.89; p < 0.0001). Also, the iron group had a 21% lower risk in terms of cardiovascular death and hospital admission for heart failure (number of events, rate per 100 patients in a year) (RR= 0.79, 95% CI 0.74 to 0.85; p < 0.00001). Concerning the adverse events, both ferric carboxymaltose and ferric derisomaltose showed a beneficial effect in reducing the cardiac disorder (RR= 0.81, 95% CI 0.76 to 0.87; p <0.0001), and (RR= 0.82, 95% CI 0.71 to 0.95; p = 0.009), respectively. Conclusions. Intravenous iron infusion in patients with heart failure has a favorable safety profile. It reduces total hospitalizations for heart failure and cardiovascular mortality, with no effect on all-cause mortality, cardiovascular mortality alone, or first-time hospitalization for heart failure.